La Colección Aquelarre: editar después del naufragio - Agustí, Lluís; Rueda Ramírez, Pedro (Caracol, 2020)
After the defeat of the Republican forces in Catalonia, almost half a million Spanish citizens crossed the border into France. In the period from 1939 to 1942, between 20,000 and 25,000 of these refugees travelled on to Mexico. During the 1940s and 1950s, a total of 111 new publishing houses were created by refugees from Spain living in Mexico, a community of people who Spanish philosopher José Gaos famously described as “los transterrados”, a term he coined to mean ‘the transplaced’ rather than simply ‘the exiled’. In Mexico City in the years between 1950 and 1954, together with other members of a tertulia of writers and activists called Aquelarre, Simón Otaola (b. 1907, San Sebastián; d. 1980, Mexico City) and José Ramón Arana [José Ruiz Borau] (b. 1905, Garrapinillos; d. 1973, Zaragoza) founded the publishing house Colección Aquelarre. As in the case of many publishers from this period, nothing remains of Colección Aquelarre’s business archives. However, the article attempts to reconstruct the history of the publisher by examining the books it published as well as other documents and accounts of Spanish exile in Mexico. The first book in the collection, Otaloa’s Unos hombres: retratos (1950), carried the label Colección Aquelarre but was published under the Ediciones Corzo imprint. All of the books after this were published directly under the name Colección Aquelarre. The last book was Ramón J. Sender’s Ariadna: novela (1955 [i.e. 1954]). The publication of the 19 books comprising the collection was self-financed by the authors. The attention to detail in the production of the books was considerable, from the lavish paper the publisher used for each book to the artisan binding of the volumes themselves, enhanced by sober but beautiful designs in attractive colours.